Directors' and officers' liability insurance and stock price crash risk - Yuan, Rongli; Sun, Jian; Cao, Feng (Journal of Corporate Finance, 2016)
We investigate the impact of directors' and officers' insurance (D&O insurance) on stock price crash risk. We find that D&O insurance in China is negatively associated with stock price crash risk. This association is robust to a series of robustness checks including the use of alternative sample, Heckman two-step sample selection model, propensity score matching procedure, fixed effects model, the inclusion of some possibly omitted variables, and bootstrap method. Further analyses show that the impact of D&O insurance on crash risk is more pronounced in firms with lower board independence, non-Big 4 auditors, lower institutional shareholdings, and weaker investor protection; and the negative relationship between D&O insurance and crash risk is not driven by the eyeball effect. Moreover, we find that D&O insurance purchase is associated with less financial restatements and more disclosure of corporate social responsibility reports. Our findings provide support to the notion that D&O insurance appears to improve corporate governance.